2020
DOI: 10.1523/jneurosci.2731-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Sensitive But More Precise Subcortical Representations Coexist with Robust Cortical Encoding of Natural Vocalizations

Abstract: Humans and animals maintain accurate sound discrimination in the presence of loud sources of background noise. It is commonly assumed that this ability relies on the robustness of auditory cortex responses. However, only a few attempts have been made to characterize neural discrimination of communication sounds masked by noise at each stage of the auditory system and to quantify the noise effects on the neuronal discrimination in terms of alterations in amplitude modulations. Here, we measured neural discrimin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 87 publications
6
40
0
Order By: Relevance
“…When we computed the average MI in 100 ms time bins (50 ms slide; see Materials and methods) of the population of A1 L4 neurons as has been done in most earlier studies [49][50][51][52], we found low information levels throughout the response duration (Fig 8A, yellow) that were not significantly different (two-sided t test with FDR correction at each time point) from population MI present in the vMGB population (Fig 8A , blue). However, consistent with a recent result showing decreasing information content in the ascending auditory pathway of anesthetized GPs [53], we found significantly lower MI levels in the A1 L2/3 population (Fig 8A , red). We confirmed that this result held over a wide range of window sizes used for analysis (S1 Fig and data in Supporting information file S9 Data).…”
Section: Emergence Of Call Feature Selectivity In A1 L2/3 Confers High Stimulusspecific Information On To Individual A1 L2/3 Neural Resposupporting
confidence: 93%
“…When we computed the average MI in 100 ms time bins (50 ms slide; see Materials and methods) of the population of A1 L4 neurons as has been done in most earlier studies [49][50][51][52], we found low information levels throughout the response duration (Fig 8A, yellow) that were not significantly different (two-sided t test with FDR correction at each time point) from population MI present in the vMGB population (Fig 8A , blue). However, consistent with a recent result showing decreasing information content in the ascending auditory pathway of anesthetized GPs [53], we found significantly lower MI levels in the A1 L2/3 population (Fig 8A , red). We confirmed that this result held over a wide range of window sizes used for analysis (S1 Fig and data in Supporting information file S9 Data).…”
Section: Emergence Of Call Feature Selectivity In A1 L2/3 Confers High Stimulusspecific Information On To Individual A1 L2/3 Neural Resposupporting
confidence: 93%
“…8A, blue). However, consistent with a recent result showing decreasing information content in the ascending auditory pathway of anesthetized GPs [53], we found significantly lower MI levels in the A1 L2/3 population (Fig. 8A, red).…”
Section: Resultssupporting
confidence: 93%
“…These results suggest that the optimal representation of call statistics likely plays a role in facilitating the identification of different sound classes even in presence of noise. Similarly, a study with guinea pigs has shown the robust discrimination in the responses to communication sounds ( Souffi et al, 2020 ). Such hypothesis aligns with earlier reports ( Chechik et al, 2006 ) but remains to be validated in the IC of the big brown bat.…”
Section: Resultsmentioning
confidence: 94%